Trabecular bone density in middle-aged women with reproductive disorders - Charissa van Zwol-Janssens; Aglaia Hage; Kim van der Ham; Birgitta K Velthuis; Ricardo P J Budde; Maria P H Koster; Arie Franx; Bart C J M Fauser; Eric Boersma; Daniel Bos; Joop S E Laven; Yvonne V Louwers (Endocrine Connections, 2023)
Besides age, estrogen exposure plays a crucial role in changes in bone density (BD) in women. Premature ovarian insufficiency (POI) and polycystic ovary syndrome (PCOS) are conditions in reproductive-aged women in which the exposure to estrogen is substantially different. Women with a history of preeclampsia (P E) are expected to have normal estrogen exposure. Within the CREw IMAGO study, we investigated if trabecular BD is different in these women because of differences in the duration of estrogen exposure. Trabecular BD was measured in thoracic vertebrae on coronary CT scans. Women with a reduced estrogen exposure (POI) have a lower BD compared to women with an intermediate exposure (PE) (mean difference (MD) −26.8, 95% CI −37.2 to −16.3). Women with a prolonged estrogen exposure (PCOS) have the highest BD (MD 15.0, 95% CI 4.3–25.7). These results support the hypothesis that the duration of estrogen exposure in these women is associated with trabecular BD. Significance statement: Our results suggest that middle-aged women with PCOS have a higher BD and women with POI have a lower BD. We hypothesized that this is due to either a prolonged estrogen exposure, as seen in women with PCOS, or a reduced estrogen exposure, as in women with POI. In the counseling of women with reproductive disorders on long-term health issues, coronary CT provides a unique opportunity to assess both coronary artery calcium score for cardiovascular screening as w ell as trabecular BD.